Constraints on Cr-PGE Mineralisation Models: Geochemical and petrological studies in the Middle Group 1 and 3 Chromitites, Western Limb, Bushveld Complex, South Africa - Arunachellan, Yogendran (Rhodes University, Faculty of Science, Department of Geology)
The Bushveld Complex in South Africa has been of interest in various research groups for decades, along with diverse theories regarding its origin, formation, and emplacement. These theories include magma mixing, contamination, and changes in the chamber's ephemeral parameters. Of interest for our current study is the formation of the middle group chromitite layers in the Western Limb. In this research, we aimed to determine the emplacement mechanism of the MG group chromitites by scrutinising the MG 1 and MG 3 layers. In core KD 151, the focus was placed on the MG 3 and MG 1 chromitite layers and their associated silicate rocks; on these regions of the core, time was spent for detailed observations. The differences and similarities of these layers were explored as the study advanced. The objectives were to determine the in-situ or proximal crystallisation of the chromitite by evaluating mineral textures and compositions. This required that we determine the characteristics of the immediate HW (hanging wall) and FW (footwall) to these chromitites, with insights into the relationship that anorthositic zones may offer and examine the PGE profiles of the chromitites in contrasting lithological settings. The sampled borehole was in the Western Limb of the Bushveld Complex; the immediate HW, chromitite layers and FW were divided into sections (2.5 x 5 cm) along selected horizons for a microscale study. The preliminary results of a study on the sub-economic Middle Group (MG) layers within the Critical Zone (CZ), contrasting the MG 1 (Lower CZ) and MG 3 (Upper CZ) chromitite layers of the Rustenburg Layered Suite of the Bushveld Complex, South Africa were analysed. The MG 3 and 1 suites of silicate rocks show disequilibrium textures between the pyroxenes and plagioclase, forming discontinuous olivine rims. These reaction rims are interpreted as products of magmatic aqueous fluid-facilitated reactions with minerals in a sub-solidus state. Deformation of the plagioclase was also noted in MG 1; this fracturing indicates either the transportation of these minerals or compaction by an overlying crystal mush. The MG 3 package of plagioclase, pyroxene and chromite compositions range from An67-78, En71-86 and Cr# of 68-84, respectively. The MG 1 package of plagioclase, pyroxene and chromite compositions are An64-91, En79-88 and Cr# of 70-80, respectively. The Cu/Pd ratio decreases from the base of the FW as it approaches the base of the chromitite, then remains low within the chromitite layer and finally increases upwards in the HW. These trends are observed in both the MG 3 and 1 package, therefore not influenced by the sulphide control. There is a decrease in both IPGE and PPGE upwards as the HW progresses into the chromitite. The FW levels of Ir and Ru increase upwards immediately adjacent to the FW contact, while Pd and Rh concentrations decrease. The whole-rock Mg# indicates a decrease in the MG 3 with a uniform increase in the HW and an erratic upward increase observed in the FW. The chondrite normalised PGE plots show a bell-shaped curve which is evident for the En content of the pyroxenes and the content of plagioclase with the highest values in the chromitite layer itself. The Cr# of the chromite decreases upwards with the highest values along the FW. The Cu/Pd ratio for MG 1 indicates chromitite control rather than sulphide control of the PGE. The whole-rock Mg# decreases in MG 1 with higher uniform values observed in the HW and FW. The geochemical and petrological data from the MG group study revealed that in situ fractional crystallisation seems unlikely as the sole mechanism for their formation in the CZ. A model is suggested in which the migration and transport of a magmatic slurry type suspension with accompanying hydrous fluids would likely have resulted in the emplacement of these chromitite packages along with the PGE mineralisation of the chromitites.
Keywords: Chromite -- South Africa Bushveld Complex; Mineralogy -- South Africa Bushveld Complex; Geochemical surveys -- South Africa Bushveld Complex